ANALISIS KESALAHAN MEMBACA HAMZAH WASHAL DAN QATHA’ PADA MATA KULIAH QIROAH MAHASISWA SEMESTER 3 JURUSAN PENDIDIKAN BAHASA ARAB UNIVERSITAS ISLAM NEGERI SYARIF KASIM RIAU - Aidillazi; Rifqi Muhammad; Akmal Athoriqi; Rahmat; Muhammad Fadhil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading skill (maharah qira'ah) is a crucial foundation for understanding Arabic texts. This study aims to identify and describe the errors in pronouncing hamzah washal and hamzah qatha’ in the Qira’ah course among the 2024 cohort students of the Arabic Education Department (PBA) at UIN Sultan Syarif Kasim Riau. A qualitative approach with a descriptive-analytic design was employed. The subjects consisted of 50 students proportionally selected from five classes who had completed Qira'ah I and II courses. Data collection methods included an Arabic text reading test, documentation of 50 voice recordings, and an online questionnaire via Google Form. The results revealed a total of 340 pronunciation errors, showing a significant imbalance between the two types of hamzah. Errors in pronouncing hamzah washal heavily dominated with 337 errors (99.11%) committed by all respondents (100%). The primary form of error was pronouncing hamzah washal with a vowel in the middle of a sentence (itsbat hamzah washal fi wasthi al-kalam) instead of eliding it, particularly in masdar (verbal noun) forms such as isti’dad and inshibat. Conversely, hamzah qatha’ errors were minimal, with only 3 errors (0.88%) committed by 2 students, in the form of omitting the hamzah sound (hadzf hamzah) in fi'il amr (imperative verbs) when preceded by the particle fa. This study concludes that students face significant difficulties in applying hamzah washal pronunciation rules compared to hamzah qatha’. It recommends evaluating teaching approaches, increasing intensive practice of sharaf and imla' rules, and implementing more applicable learning methods by lecturers.